Sophora flavescens Aiton Decreases MPP+-Induced Mitochondrial Dysfunction in SH-SY5Y Cells - Kim, Hee-Young; Jeon, Hyongjun; Kim, Hyungwoo; Koo, Sungtae; Kim, Seungtae (Frontiers in Aging Neuroscience, 2018)
Sophora flavescens Aiton (SF) has been used to treat various diseases including fever and inflammation in China, Korea and Japan. Several recent reports have shown that SF has anti-inflammatory and anti-apoptotic effects, indicating that it is a promising candidate for treatment of Parkinson’s disease (PD). We evaluated the protective effect of SF against neurotoxin 1-methyl-4-phenylpyridinium ion (MPP+) -induced mitochondrial dysfunction in SH-SY5Y human neuroblastoma cells, an in vitro PD model. SH-SY5Y cells were incubated with SF for 24 h, after which they were treated with MPP+. MPP+-induced cytotoxicity and apoptosis were confirmed by 3-(4,5-dimethyl-thiazol-2-yl)-2,5-diphenyl tetrazolium bromide assay and terminal deoxynucleotidyl transferase-mediated biotinylated UTP nick end labeling assay. MitoSOX red mitochondrial superoxide indicator, tetramethylrhodamine methyl ester perchlorate, and Parkin, PTEN-induced putative kinase 1 (PINK1), and DJ-1 immunofluorescent staining were conducted to confirm the mitochondrial function. In addition, western blot was performed to evaluate apoptosis factors (Bcl-2, Bax, caspase-3 and cytochrome c) and mitochondrial function-related factors (Parkin, PINK1, and DJ-1). SF suppressed MPP+-induced cytotoxicity, apoptosis and collapse of mitochondrial membrane potential by inhibiting the increase of reactive oxidative species (ROS) and DNA fragmentation, and controlling Bcl-2, Bax, caspase-3 and cytochrome c expression. Moreover, it attenuated Parkin, PINK1, and DJ-1 expression from MPP+-induced decrease. SF effectively suppressed MPP+-induced cytotoxicity, apoptosis and mitochondrial dysfunction by regulating generation of ROS, disruption of mitochondrial membrane potential, mitochondria-dependent apoptosis, and loss or mutation of mitochondria-related PD markers including Parkin, PINK1 and DJ-1.